2021
DOI: 10.1097/md.0000000000025123
|View full text |Cite
|
Sign up to set email alerts
|

Viral shedding in gastroenteritis in children caused by variants and novel recombinant norovirus infections

Abstract: Human norovirus (NoV) is the leading cause of acute gastroenteritis and the rapid transmission of NoV renders infection control problematic. Our study aimed to investigate viral shedding in gastroenteritis in children caused by variants of emerging norovirus strains infections. We used RNA-dependent RNA polymerase (RdRp) sequencing to measure NoV genome copies in stool to understand the relationship between the clinical manifestations and viral shedding in hospitalized patients. The near full-length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(21 reference statements)
0
4
0
2
Order By: Relevance
“…The peak shedding of norovirus has been reported to occur between symptom onset to 5 days after infection [ 25 ], with over 10 9 copies of viral particles shed in one gram of feces [ 6 ]. Cheng et al reported that among hospitalized pediatric patients, norovirus viral load increased between days 2 and 9 following illness onset, and most norovirus shedding in feces ceased by day 15, with an average viral load of 7.25 log genome copies/mL for all samples [ 26 ]. In our study, we did not observe an increase in viral load after illness onset, but the median viral load of norovirus on Day 0 was 9.9 log GE copies/g stool, and it remained persistently high on Day 5 (9.7 log GE copies/g stool).…”
Section: Discussionmentioning
confidence: 99%
“…The peak shedding of norovirus has been reported to occur between symptom onset to 5 days after infection [ 25 ], with over 10 9 copies of viral particles shed in one gram of feces [ 6 ]. Cheng et al reported that among hospitalized pediatric patients, norovirus viral load increased between days 2 and 9 following illness onset, and most norovirus shedding in feces ceased by day 15, with an average viral load of 7.25 log genome copies/mL for all samples [ 26 ]. In our study, we did not observe an increase in viral load after illness onset, but the median viral load of norovirus on Day 0 was 9.9 log GE copies/g stool, and it remained persistently high on Day 5 (9.7 log GE copies/g stool).…”
Section: Discussionmentioning
confidence: 99%
“…По степени выраженности обезвоживания: I степень -74%, II степень -4%, III степень -22%. Микст-формы РВИ выявлялись в виде гастроэнтерита в 80 (88,9%) случаях и энтероколита -в 10 (11,1%) в среднетяжёлой (81%) и тяжёлой (19%) формах [20][21][22]. По степени выраженности -с эксикозом I (63%), II (18%), III (19%) степени.…”
Section: результатыunclassified
“…Infection follows a fecal-oral route, with infection possible with small amounts of virion exposure [124][125][126][127]. Once infected, children may shed virus for weeks post-infection [128]. Human norovirus is highly transmissible, especially in enclosed locations with a high density of people [103,129].…”
Section: Virus Backgroundmentioning
confidence: 99%